Nonpharmaceutical Interventions Used to Control COVID-19 Reduced Seasonal Influenza Transmission in China. (8th September 2020) - Lei, Hao; Xu, Modi; Wang, Xiao; Xie, Yu; Du, Xiangjun; Chen, Tao; Yang, Lei; Wang, Dayan; Shu, Yuelong
Abstract: To suppress the ongoing COVID-19 pandemic, the Chinese government has implemented nonpharmaceutical interventions (NPIs). Because COVID-19 and influenza have similar means of transmission, NPIs targeting COVID-19 may also affect influenza transmission. In this study, the extent to which NPIs targeting COVID-19 have affected seasonal influenza transmission was explored. Indicators of seasonal influenza activity in the epidemiological year 2019–2020 were compared with those in 2017–2018 and 2018–2019. The incidence rate of seasonal influenza reduced by 64% in 2019–2020 ( P < .001). These findings suggest that NPIs aimed at controlling COVID-19 significantly reduced seasonal influenza transmission in China.